Efisiensi Pemasaran Ternak Sapi Potong Di Kota Palu Provinsi Sulawesi Tengah - Hijrianti, Hijrianti; Syukur, Suharno H.; Mujayin, Yudi (Mitra Sains, 2023)
This research aims to analyze the marketing efficiency of beef cattle in Palu City. This research was conducted at the West Palu Regency Animal Market and the Animal Market in Tawaeli Regency for 3 months, namely March to May 2022. The research method used in this research was a field survey method with a supporting instrument in the form of a questionnaire. Sampling was carried out by means of snowball sampling or sampling by taking an approach to finding key informants. The research results show that there are 5 marketing channels for beef cattle in Palu City, Marketing Channels I, II, III and IV are classified as efficient, this can be seen from the marketing efficiency value for beef cattle in Palu City which shows that marketing channel I is 0.96%, Channel Marketing II was 1.77%, Marketing Channel III was 2.10%, Marketing Channel IV was 3.45%. Meanwhile, the inefficient marketing channel for beef cattle in Palu City is marketing channel V because its marketing efficiency value is more than 5%, namely 8.49%. The factors that influence the marketing efficiency of beef cattle in the city of Palu are age (X1) and length of business (X2), where the results of simultaneous testing (together) of X1 and X2 on Y then together have a significant influence on efficiency marketing and If tested on each variable, the results show that the factors age (X1) and length of business (X2) each have a very significant influence on marketing efficiency (Y).